Social Support of Organ Donor Families in China: A Quantitative and Qualitative Study - Luo, Aijing; He, Haiyan; Xu, Zehua; Deng, Xuantong; Xie, Wenzhao (Frontiers in Public Health, 2021)
Background: Donor families experienced a difficult time during and after the process of organ donation. There is a necessity to understand the support they received and what they need to help them get through a painful time. This study aimed to investigate the social support level and social support needs of the donor families in China. Methods: A cross-sectional study was conducted among 102 donor families using a questionnaire to investigate their demographics and social support level. To further understand their social support needs, in-depth interviews were conducted among 9 donor families. Results: Findings of the study showed that (1) Most of the family members (74, 72.6%) lacked social support, and only a small number of families (28, 27.5%) received sufficient social support (2). The coping style had an impact on the overall social support level (P = 0.014) (3). There was a lack of emotional support, information support and material support toward the donor's family members. Both emotional support and material support are significantly needed. Conclusions: The overall social support level remained insufficient and the utilization degree of social support was low. Organ donor families are in desperate need of material and emotional support. The level of social support is largely influenced by the donor familie's coping style. Compared with a negative coping style, donor families who adopted a positive coping style acquire more social support.